Assessment of complications of open treatment of mandibular condylar fractures - Muhammad Adil Asim; Waseem Ahmed; Muhammad Wasim Ibrahim; Syed Gulzar Ali Bukhari; Muhammad Nazir Khan (Journal of the Pakistan Medical Association, 2021)
Objective: To analyze the complications of open treatment of mandibular condylar fractures via various surgical approaches. Methods: The study was conducted at the department of oral and maxillofacial surgery at Armed forces institute of dentistry, Rawalpindi. All adult patients with moderate to severely displaced mandibular condylar fractures were included in our study. Open reduction and internal fixation of fractures was performed by five consultant maxillofacial surgeons via four surgical approaches. Patients were assessed for complications of open treatment in terms of facial nerve paresis, unaesthetic scar, salivary fistula/sialocele, trismus and malocclusion 6 months postoperatively. Frequency and percentages were calculated for the categorical variables while chi square test was applied to compare the categorical variables. Continuous...